Respuesta :

Answer:

[tex]66\frac{2}{3}\% = \frac{2}{3}[/tex]

Step-by-step explanation:

Given:

[tex]66\frac{2}{3}\%[/tex]

Required

Express in its simplest form

[tex]66\frac{2}{3}\%[/tex]

Convert to improper fraction

[tex]66\frac{2}{3}\% = \frac{66*3+2}{3}\%[/tex]

[tex]66\frac{2}{3}\% = \frac{198+2}{3}\%[/tex]

[tex]66\frac{2}{3}\% = \frac{200}{3}\%[/tex]

%  means [tex]\frac{1}{100}[/tex]

So, we have:

[tex]66\frac{2}{3}\% = \frac{200}{3} * \frac{1}{100}[/tex]

[tex]66\frac{2}{3}\% = \frac{200*1}{3*100}[/tex]

[tex]66\frac{2}{3}\% = \frac{2*1}{3*1}[/tex]

[tex]66\frac{2}{3}\% = \frac{2}{3}[/tex]

The expression has been finally simplified